A Prospective Clinical Study of Ferric Citrate Hydrate for Chronic Heart Failure with Iron Deficiency Anemia - Akira Sezai; Hisakuni Sekino; Makoto Taoka; Kazuaki Obata; Sakie Kanno; Masashi Tanaka (Life)
Background: The efficacy of intravenous iron preparations for chronic heart failure with iron deficiency has been reported, but the efficacy of oral iron preparations has not been demonstrated. In this study, we conducted a prospective clinical study using ferric citrate hydrate tablets in patients with chronic heart failure complicated by iron deficiency anemia. Methods and Results: A prospective study was conducted using ferric citrate hydrate in patients with chronic heart failure complicated by iron deficiency anemia. The registered patients were divided into two groups: those administered ferric citrate hydrate and those switched from iron sulfate sustained-release to ferric citrate hydrate. The primary endpoint was hemoglobin level. The secondary endpoints included hematocrit, serum iron, saturation, ferritin, and cardiac-, renal-, and hepatic-related biomarkers. A total of 141 patients were enrolled in this study, including 95 patients who were newly administered ferric citrate hydrate and 46 patients who were switched from iron sulfate sustained-release to ferric citrate hydrate. Conclusions: Ferric citrate hydrate significantly increased hemoglobin, serum iron, transferrin saturation (TSAT), and ferritin levels, and decreased atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels. Ferric citrate hydrate could be continued without side effects such as gastrointestinal symptoms. Improvement in iron metabolism and anemia due to iron supplementation with ferric citrate hydrate led to improvement in heart failure biomarkers.